2019
DOI: 10.3892/ol.2019.10495
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA profiling and bioinformatics analyses reveal upregulated miRNAs in gastric cancer

Abstract: Gastric cancer is one of the most common malignancies in China and exhibits a poor prognosis. The most significant challenge for gastric cancer treatment is the absence of early diagnostic biomarkers. MicroRNAs (miRNAs) are small non-coding RNAs, which possess clinical value in a number of different types of cancer. The current study identified 13 miRNAs (hsa-miR-22, hsa-miR-545, hsa-let-7i, hsa-miR-15b, hsa-miR-221, hsa-miR-196a, hsa-miR-20a, hsa-miR-196b, hsa-miR-93, hsa-miR-19a, hsa-miR-503, hsa-miR-106b an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…However, the potential association between the miR-15b family and GC is controversial. miR-15b has been shown to be downregulated in SGC7901/DDP cells [46] and gastric adenoma [47], while Yuan et al [48] has shown the significant overexpression of miR-15b in GC, which was found by analyzing 1000 GC samples included in four public datasets. In addition, miR-15b-5p impact on invasion, migration and proliferation of GC cells with high miR-15b-5p levels in GC cell lines, tissues and serum samples were confirmed by Zhao et al [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential association between the miR-15b family and GC is controversial. miR-15b has been shown to be downregulated in SGC7901/DDP cells [46] and gastric adenoma [47], while Yuan et al [48] has shown the significant overexpression of miR-15b in GC, which was found by analyzing 1000 GC samples included in four public datasets. In addition, miR-15b-5p impact on invasion, migration and proliferation of GC cells with high miR-15b-5p levels in GC cell lines, tissues and serum samples were confirmed by Zhao et al [49].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are a class of naturally occurring small noncoding RNAs which are 19-25 nucleotides (19-25 nt) in length. They have recently been reported to be frequently dysregulated in various cancers [4][5][6][7] . Accumulating evidences indicate that circulating miRNAs could be stable blood-based markers for cancer diagnosis 8 .…”
Section: Serum Micrornas (Mirnas) Have Been Reported As Novel Biomarkmentioning
confidence: 99%
“…miRNAs (or microRNAs or miRs) are small non-coding RNAs which regulate gene expression at the post-transcriptional level by inhibiting the stability or the transcriptional efficiency of target genes. Through their action of regulating the genome, miRNAs are key players in many physiopathological mechanisms, particularly cancers ( He and Hannon, 2004 ; Yuan et al, 2019 ). To identify if miRNAs are involved in the modification of MEC features, we performed miRNA expression profiling analyses on the MECs co-cultured either with hASCs or MAs.…”
Section: Resultsmentioning
confidence: 99%